The determinants of price in 3G spectrum auctions - Madden, Gary; Suenaga, Hiroaki (Routledge, 2016)
This article examined the empirical relationship between prices paid for national 3G wireless licenses when spectrums were sold by auction. The reduced-form modelling approach was based on the premise that auction design features can, and do, affect both final (revenue) and intermediate (viz., auction competitiveness and license assignment) auction outcomes. Importantly, the analysis recognizes, and explicitly allows for, the endogeneity of bidder entry and sample selection arising from an absence of bidding. Generally, these key features have only received attention in isolation. In particular, the study addressed the principal question of: which regulator chosen auction design variables determine prices paid in spectrum auctions? The analysis showed that flexible-package formats increased prices paid, and that higher reserve prices had a dampening effect. The article also showed that longer license terms and more competitive auctions (as measured by the bidders-to-licenses ratio) enhance prices paid.